Congenital Heart Disease and Adolescence - Schwerzmann, Markus; Thomet, Corina; Moons, Philip (Congenital Heart Disease in Adolescents and Adults, 2016)
This book provides medical care givers with detailed information on those aspects of adolescence that are of significance in the setting of congenital heart disease (CHD), from anatomic and physiologic changes to behavioral issues. In addition, it explains how care should be organized in order to ensure that the needs of adolescents with CHD are fully met. Both theoretical and practical aspects of the switch from a pediatric to an adult health perspective in CHD patients are outlined in detail, drawing attention to the importance of a structured transition plan and other best practices. As the survival of children with complex CHD improves further, the number of adolescents with CHD will continue to grow. Awareness of the challenges that these patients face is essential if they are to be appropriately prepared to assume adult roles and functioning. Readers will find Congenital Heart Disease and Adolescence to be an excellent source of relevant knowledge and guidance. It has been written for a broad audience, bearing in mind that care in adolescents is an interdisciplinary task involving close collaboration among physicians, specialists, nurses, patients, and relatives.